Airflow obstruction as a marker of adverse prognosis in rheumatoid arthritis - Guiot, Julien; Henket, Monique; Ernst, Marie; Seidel, Laurence; Winandy, Marie; Denis, Anna; Frix, Anne-Noëlle; Gester, Fanny; Thys, Marie; Giltay, Laurie; Garah, Omaima; Njock, Makon-Sébastien; et al. (Frontiers in Medicine, 2023)
Objectives: We wanted to explore obstructive lung disease (OLD) in RA and its impact on morbi-mortality in these patients. Methods: Our retrospective study included 309 patients suffering from RA with either obstructive (O-RA) or non-obstructive patterns (non-O-RA). OLD was defined based on the Tiffeneau index at the first available pulmonary functional test (PFT). The survival was calculated since the first PFT and represented by a Kaplan-Meier curve. The comparison between the populations considered was performed by the Log-Rank test. Results: Out of the 309 RA patients, 102 (33%) had airway obstruction on the first PFT. The overall survival time since the first PFT was significantly lower in the O-RA group than in the non-O-RA group (n= 207) (p <0.001). The median survival time was 11.75 years in the O-RA group and not defined in the non-O-RA group. Multivariate analysis identified OLD as an independent risk factor for mortality (HR 2.20; 95% CI 1.23-3.92, p<0.01). Conclusion: Airway obstruction is an independent risk factor of mortality in RA and should be considered an early marker of poor prognosis. Further prospective studies are needed to determine the best management for those patients.